Tissue cell stress response to obesity and its interaction with late gestational diet - Saroha, Vivek; Dellschaft, Neele S.; Keisler, Duane H.; Gardner, David S.; Budge, Helen; Sebert, Sylvain P.; Symonds, Michael E. (CSIRO Publishing, 2018)
Intra-uterine growth restriction in late pregnancy can contribute to adverse long term metabolic health in the offspring. We utilised an animal (sheep) model of maternal dietary manipulation in late pregnancy, combined with exposure of the offspring to a low activity, obesogenic environment after weaning, to characterise the effects on glucose homeostasis. Dizygotic twin-pregnant sheep were either fed to 60% of requirements (nutrient restriction (R)) or fed ad libitum (~ 140% of requirements (A)) from 110 days gestation until term (~147d). After weaning (~3 months of age), their offspring were kept in either a standard (in order to remain lean) or low activity, obesogenic environment. R mothers gained less weight and produced smaller offspring. As adults, obese offspring were heavier and fatter with reduced glucose tolerance, irrespective of maternal diet. Molecular markers of stress and autophagy in liver and adipose tissue were increased with obesity, with gene expression of hepatic Grp78 and of omental Atf6, Grp78 and Edem1 only being increased in R offspring. In conclusion, the adverse effect of juvenile onset obesity on insulin responsive tissues can be amplified by previous exposure to a suboptimal nutritional environment in utero, thereby contributing to earlier onset of insulin resistance.